Reliable Hybrid Small-Signal Modeling of GaN HEMTs Based on Particle-Swarm-Optimization - Hussein, Ahmed S.; Jarndal, Anwar H. (IEEE transactions on computer-aided design of integrated circuits and systems, 2018)
This paper presents an efficient parameter extraction method applied to GaN high electron mobility transistors. The procedure only relies on S -parameter measurements at cold bias conditions to extract the extrinsic parameters of a 19-element small-signal model. Hybrid technique of particle-swarm-optimization and direct fitting has been developed and implemented. The extraction procedure has been optimized to consider measurements uncertainty and improve the reliability of the extraction. The procedure has been validated by multibias extraction for different device sizes. A very good agreement between simulations and measurements has been obtained.